Association between toothbrushing frequency and dental caries and tooth loss in adolescents: a cohort study - Carolina Doege BRUSIUS; Luana Severo ALVES; Marisa MALTZ (Sociedade Brasileira de Pesquisa Odontológica, 2023)
Abstract This cohort study assessed the association between toothbrushing frequency and the increment of dental caries and tooth loss in a population-based sample of southern Brazilian adolescents, to investigate whether there is any additional benefit in performing a third daily brushing. At baseline, 1,528 12-year-old schoolchildren attending 42 schools were examined for gingivitis and dental caries, and answered a questionnaire. After a mean period of 2.5 years, 801 schoolchildren were re-examined. Dental caries and tooth loss increment were outcomes of the study. The main predictor variable was toothbrushing frequency (≥3 times/day vs. twice/day or ≤1 time/day). Poisson regression models were used to estimate the risk for caries and tooth loss increment. Incidence risk ratios (IRR) and 95% confidence intervals (CI) were estimated. The final model adjusted for sociodemographic, behavioral, and clinical variables showed that brushing twice/day afforded 40% greater risk (IRR = 1.40; 95%CI: 1.02-1.92) for caries increment than ≥3 times/day. Regarding the tooth loss increment, adolescents who brushed their teeth twice/day had a fourfold greater risk (IRR = 3.92; 95%CI: 1.23-12.49) than those who brushed ≥ 3 times/day. Sex, school type, and gingivitis were found to act as effect modifiers, inasmuch as a third daily brushing presented advantages against tooth loss only for girls, public school attendees, and those with ≥ 50% of bleeding sites. This study suggests that adolescents benefit from a third daily toothbrushing. Increasing brushing frequency to 3 times/day may be a suitable strategy to control dental caries and tooth loss among high-risk adolescents.